Pendidikan dalam pemikiran K. H. Ahmad Dahlan - Dewi, Khristi Rosika; Istiq’faroh, Nurul; Hendratno (CV. Kurnia Grup, 2023)
This research examines KH Ahmad Dahlan's views on education, especially in Indonesia. The method used in this research is the literature study method. The article explores the positive impact the application of his educational theory has on the general public and the country. KH Ahmad Dahlan's concept of education leads to a way of building a generation that is not only intellectually intelligent, but also ethical and responsible, in the form of integration of Islamic values in the education system. The results of this article briefly highlight the need for an in-depth understanding of KH Ahmad Dahlan's perspective on education in order to effectively manage education reform. The principles and standards of education followed by the subject, which include religious, moral, and behavioral aspects. Ahmad Dahlan explained that education is about the development of character and spirituality as well as the transfer of knowledge. Seeing the need for an in-depth understanding of the educational perspective of KH. Ahmad Dahlan in order to effectively manage education reform. This research has implications for strengthening the role of education as a means of nation building.